3D Dip‐Pen Nanolithography. Issue 8 (5th January 2022) - Liu, Guoqiang; Rong, Mingming; Hu, Hong; Chen, Lina; Xie, Zhuang; Zheng, Zijian
Abstract: Dip‐pen nanolithography (DPN) can directly write a variety of materials on the substrates at the sub‐50 nm to micrometer length scale. While this tool has been extensively exploited to construct functional nanostructures and address important scientific questions, extending the capability from low‐dimensional molecular patterning to direct additive 3D manufacturing has yet to be demonstrated. In this work, the development of 3D‐DPN is reported to enable the microscale 3D printing capability via designing a rapidly UV‐curable liquid copolymer ink with appropriate viscoelastic properties. Two categories of 3D printing strategies via patterning dot and line pixels are explored, through which micrometer‐high, arbitrary 3D structures could be programmed to generate. It is believed that this development will arouse the fundamental research and functional application interest in the field of tip‐based additive 3D nanofabrication. Abstract : 3D dip‐pen nanolithography (3D‐DPN), which can construct micro/nano 3D structures (e.g., pyramid) on the substrate in a direct‐write manner, is developed by synthesizing a new photocrosslinked copolymer as ink and planning two different printing ways including dot and line strategies. This development promotes the DPN technology one step forward from previous 2D patterning to present 3D construction.